Gender differences with anxiety, perceived competence, and grit in collegiate track and field throwers - Criticos, M.; Layne, T.; Simonton, K.; Irwin, C. (Journal of Physical Education and Sport, 2020)
Much research has been conducted on methods for enhancing sports performance. One area that has been examined is athletes Grit. Grit can be described as a combination of one`s ability to overcome obstacles they encounter in their goal pursuit and continued persistence towards the goal over time. The intent of this study was to examinegender differences regarding self-perceived grit and meet performance in male and female collegiate track and field throwers. Subjects consisted of nine university track and field student-athlete throwers (5 males; 4 female). A mixed methods approach was applied. Quantitative measures included tracking athletes for 6 weeks. Grit and competition performance information was collected bi-weekly (3 times) to evaluate potential trends. Additionally, trait characteristics, perceived anxiety and competence were collected on each athlete. Qualitative measures involved gender group interviews at the end of the season to address potential variables associated with grit. Results indicated that there were differences between genders anxiety, competence, grit and their throwing performances. Grit scores indicated that motivational levels are impacted by overall performance and can shift from week to week. Female athletes were impacted by external factors such as stress, drama, and fear. Anxiety can impact overall grit, which should lead coaches to develop methods for helping athletes deal with anxiety. These results can be applied to help coaches and other caring individuals develop their athletes. Methods should be implemented to help avoid pitfalls associated with male/female athletes. By using the Grit scale, coaches can better prepare to meet the needs of each athlete and adjust their training throughout the season.